Characteristic polynomial of path semigraphs - Murugesan N.; Narmatha D. (Utilitas Mathematica, 2017)
In order to study the structural properties of graphs various matrices are associated to the graphs. In this paper, various properties of semigraphs and characteristic polynomial corresponding to e-Adjacency matrix of path semigraphs have been discussed. © 2015 Utilitas Mathematics.